Financial Incentives for Smoking Cessation in Pregnancy. Issue 5 (May 2015) - Tappin, David; Bauld, Linda; Purves, David; Boyd, Kathleen; Sinclair, Lesley; MacAskill, Susan; McKell, Jenniffer; Friel, Brenda; McConnachie, Alex; de Caestecker, Linda; Tannahill, Carol; Radley, Andrew; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT Each year, 25, 000 spontaneous miscarriages are associated with smoking during pregnancy. While there are many medical approaches to smoking cessation, they have not proven to be the particularly effective. A recent Cochrane systematic review suggests that financial incentives may be effective in helping pregnant smokers quit. The current study explored the efficacy and cost-effectiveness of financial incentives added to routine specialist pregnancy NHS "Stop Smoking Services" that provide assistance to pregnant women to quit smoking. The design of this study used a phase II therapeutic randomized controlled trial in a single center that covered a wide geographical location. Women eligible for the study were smokers who had a carbon monoxide measurement of 7 ppm, were 16 years or younger, at less than 24 weeks' gestation, and resident in NHS Greater Glasgow and Clyde. All eligible women were allocated to a control group (306) or incentives (306). The routine specialist pregnancy care consisted of a face-to-face appointment followed by 4 weekly phone support calls and free nicotine replacement therapy for 10 weeks, with a confirmation of smoking status at 4 and 12 weeks of agreed quit date. Control groups were offered routine support; an intervention group received a £50 voucher for attending all appointments and to set a quit date. The incentive group was also offered £400 shopping vouchers if they engaged with stop smoking services or quit. Those who remained abstinent, confirmed by a carbon monoxide breath test (<10 ppm), in the intervention group were also given additional £50 vouchers at 2 weeks and £100 vouchers at 12 weeks. A final £200 voucher was given to the incentive group when confirmed smoking abstinence at quit date. In the primary outcome assessment, there was a significant difference between the 2 groups. More women had stopped smoking in the incentives group (22.5% vs 8.6 %; P < 0.001), and relative risk of not smoking at the end of pregnancy was 2.63 (95% confidence interval, 1.73–4.01). Secondary outcome assessment revealed a higher rate of continued abstinence 4 weeks after quit date in the incentives group. This study suggests that financial incentives can aid women to quit smoking during pregnancy and are more effective than other approaches currently recommended. The cost of this incentive is also below the current UK National Health Service threshold and is a cost-effective option in the short term. Smoking during pregnancy may prevent both maternal and neonatal complications, and financial incentives should be considered as a more effective method to avoid these conditions than the current incentives provided.